The Influence of Economic Factors on the Human Development Index in East Kalimantan Province - Tiara Dela Safira; Muliati (FORUM EKONOMI: Jurnal Ekonomi, Manajemen dan Akuntansi, 2026)
This study aims to determine economic factors such as the regional minimum wage, economic growth rate, poverty, and open unemployment rate to the human development index in East Kalimantan in 2015-2024. This research method is a quantitative method using secondary data. Panel data regression analysis technique with a Fixed Effect Model (FEM) approach through EViews 13 software. These findings indicate that partially the regional minimum wage and the rate of economic growth have a significant positive effect on the human development index in East Kalimantan, while poverty and open unemployment have a negative but insignificant effect on the human development index in East Kalimantan. Simultaneously, the regional minimum wage, economic growth rate, poverty, and open unemployment rate have a significant effect on the human development index in East Kalimantan in 2015-2024